INCREASING BRAND AWARENESS AND IMPLEMENTING MARKETING MANAGEMENT STRATEGIES FOR DEPOK CITY MSMEs - Ridwan Taufik Hidayat; Lucky Anggara; Ratna Diah; Rossa Anjalina Soraya; Sri Henny Romauli Sitepu; Yayan Sudaryana; Zulfitra, Zulfitra (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
In the era of globalization and digitalization, Micro, Small, and Medium Enterprises (MSMEs) face significant challenges in brand awareness and marketing management strategies, especially at the local level. This research focuses on MSMEs in Depok, aiming to analyze and identify effective strategies to enhance brand awareness and implement marketing management practices. The study employed both qualitative and quantitative approaches to collect and analyze data. The findings revealed that most MSMEs in Depok face difficulties in gaining brand recognition due to limited capital and knowledge of digital marketing. The training program on "Enhancing Brand Awareness and Implementing Marketing Management Strategies" led to a 78.72% improvement in participants' understanding, indicating the effectiveness of the training materials. Participants also reported high satisfaction levels, with an average score of 4.6 out of 5, reflecting the training's relevance to their needs. This study suggests that MSMEs should invest in market research, optimize the use of social media, and develop creative content to enhance brand visibility. Collaborations with local influencers and organizing community activities are recommended to strengthen brand positioning. The research concludes that a comprehensive approach, including digital marketing training and strategic planning, is essential for MSMEs in Depok to achieve sustainable growth